Shelf life evaluation of formulated cookies from Hanjeli (Coix lacryma-jobi L.) and Moringa leaf flour (Moringa oleifera) - Iwansyah, Ade Chandra; Melanie, Dwi; Cahyadi, Wisnu; Indrianingsih, Anastasia Wheni; Khasanah, Yuniar; Indriati, Ashri; Hazrulrizawati, Abd Hamid; Izzah Hayati, Yahya (Elsevier Ltd, 2022)
Hanjeli (Coix lacryma-jobi L.) and moringa leaf (Moringa oleifera) remain underutilised despite their high nutritional value for food. In the present research, cookies made from hanjeli (Coix lacryma-jobi L.) with moringa leaf flour (Moringa oleifera) have been developed. Hanjeli cookies were measured for nutritional composition and shelf life assessment. The shelf life evaluation of hanjeli-moringa cookies was calculated using two approaches, which were accelerated shelf life testing (ASLT) methods with critical moisture content and the Arrhenius method. The results of the nutritional composition analysis showed that hanjeli-moringa cookies contain protein (9.14%), fat (24.67%), carbohydrates (61.62%), crude fibre (4.85%), and energy (505.01 Kcal). Using the Arrhenius method, the shelf life of hanjeli-moringa cookies was 95.46 days at room temperature and 97.63 days at 20 °C. Meanwhile, the shelf life of cookies using the critical moisture content approach was 170.57 days. Shelf life is influenced by initial moisture content, critical water content of the product, packaging surface area and permeability, saturated vapour pressure, and slope sorption isotherm curve. The formulated cookies have significant amounts of nutrients that are acceptable and safe for consumption, with guaranteed desirable sensory properties. The result of this study shows that hanjeli-moringa cookies can be used as an alternative food for people who need high energy in a practical way of serving or ready to eat.